1981
DOI: 10.1007/bf02603417
|View full text |Cite
|
Sign up to set email alerts
|

Palliative resection for colorectal carinoma

Abstract: In an attempt to identify those patients who would benefit from palliative resection of the colon or rectum and those who would not, an analysis of ten years of resections was undertaken. For the 81 patients who underwent palliative resection, the operative mortality was 10 per cent and the postoperative morbidity was 50 per cent. The mean survival was 11.4 months and the median survival nine months. Poor prognostic factors deduced were patients with extensive liver metastases, those over the age of 75 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
71
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 10 publications
10
71
0
Order By: Relevance
“…There is a high rate of postoperative mortality (12-14%) and morbidity (60%). 48,49 Surgery is often incomplete with persistent and second local recurrence rates of 50 -62%. 50 However, 25% of carefully selected patients who undergo complete resection of tumor can be salvaged and are long-term survivors.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high rate of postoperative mortality (12-14%) and morbidity (60%). 48,49 Surgery is often incomplete with persistent and second local recurrence rates of 50 -62%. 50 However, 25% of carefully selected patients who undergo complete resection of tumor can be salvaged and are long-term survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery to manage acute symptoms of bleeding, obstruction and perforation has been advocated for this group. However, the management of asymptomatic patients with stage IV colorectal cancer remains controversial 2,3 . Patient-dependent factors (performance status, co-morbid disease) and extent of distant metastasis are among the considerations that impact on the decision to proceed with surgical management in such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Both trials demonstrated a statistically significant survival advantage for patients treated with surgery (11.1 vs. 8.1 months, P 5 0.05; 17 vs. 7 months, P 5 0.03, respectively) [14,15]. Longer survival rates have also been shown in studies of gastric cancer [16][17][18][19], ovarian cancer [20], and colorectal carcinoma [21][22][23].…”
Section: Introductionmentioning
confidence: 99%